When do herbivores affect plant invasion? Evidence for the natural enemies and biotic resistance hypotheses - Maron, John L.; Vilà, Montserrat (Oikos, 2001)
Two venerable hypotheses, widely cited as explanations for either the success or failure of introduced species in recipient communities, are the natural enemies hypothesis and the biotic resistance hypothesis. The natural enemies hypothesis posits that introduced organisms spread rapidly because they are liberated from their co-evolved predators, pathogens and herbivores. The biotic resistance hypothesis asserts that introduced species often fail to invade communities because strong biotic interactions with native species hinder their establishment and spread. We reviewed the evidence for both of these hypotheses as they relate to the importance of non-domesticated herbivores in affecting the success or failure of plant invasion. To evaluate the natural enemies hypothesis, one must determine how commonly native herbivores have population-level impacts on native plants. If native herbivores seldom limit native plant abundance, then there is little reason to think that introduced plants benefit from escape from these enemies. Studies of native herbivore-native plant interactions reveal that plant life-history greatly mediates the strength with which specialist herbivores suppress plant abundance. Relatively short-lived plants that rely on current seed production for regeneration are most vulnerable to herbivory that reduces seed production. As such, these plants may gain the greatest advantage from escaping their specialist enemies in recipient communities. In contrast, native plants that are long lived or that possess long-lived seedbanks may not be kept "in check" by native herbivores. For these species, escape from native enemies may have little to do with their success as exotics; they are abundant both where they are native and introduced. Evidence for native herbivores providing biotic resistance to invasion by exotics is conflicting. Our review reveals that: 1) introduced plants can attract a diverse assemblage of native herbivores and that 2) native herbivores can reduce introduced plant growth, seed set and survival. However, the generality of these impacts is unclear, and evidence that herbivory actually limits or reduces introduced plant spread is scarce. The degree to which native herbivores provide biotic resistance to either exotic plant establishment or spread may be greatly determined by their functional and numerical responses to exotic plants, which we know little about. Generalist herbivores, through their direct effects on seed dispersal and their indirect effects in altering the outcome of native-non-native plant competitive interactions, may have more of a facilitative than negative effect on exotic plant abundance.